Long-term neurodevelopmental outcome in high-risk newborns in resource-limited settings: a systematic review of the literature. (August 2015) - Milner, K. M.; Neal, E. F. G.; Roberts, G.; Steer, A. C.; Duke, T.
Abstract : Background: Improving outcomes beyond survival for high-risk newborns in resource-limited settings is an emerging challenge. Global estimates demonstrate the scale of this challenge and significant gaps in morbidity outcome data in high mortality contexts. A systematic review was conducted to document the prevalence of neurodevelopmental impairment in high-risk newborns who were followed up into childhood in low- and middle-income countries. Methods: High-risk newborns were defined as low, very or extremely low birthweight, preterm infants or those surviving birth asphyxia or serious infections. Electronic databases were searched and articles screened for eligibility. Included articles were appraised according to STROBE criteria. Narrative review was performed and median prevalence of key neurodevelopmental outcomes was calculated where data quality allowed. Results: 6959 articles were identified with sixty included in final review. At follow-up in early childhood, median estimated prevalence (inter-quartile range) of overall neurodevelopmental impairment, cognitive impairment and cerebral palsy were: for survivors of prematurity/very low birthweight 21.4% (11.6–30.8), 16.3% (6.3–29.6) and 11.2% (5.9–16.1), respectively, and for survivors of birth asphyxia 34.6% (25.4–51.5), 11.3% (7.7–11.8) and 22.8% (15.7–31.4), respectively. Only three studies reporting outcomes following newborn serious bacterial infections were identified. There was limited reporting of important outcomes such as vision and hearing impairment. Major challenges with standardised reporting of key exposure and developmental outcome variables and lack of control data were identified. Conclusion: Understanding the limitations of the available data on neurodevelopmental outcome in newborns in resource-limited settings provides clear direction for research and efforts to improve long-term outcome in high-risk newborns in these settings.